Impact of chronic kidney disease on the pharmacodynamic and pharmacokinetic effects of ticagrelor in patients with diabetes mellitus and coronary artery disease. Issue 5 (11th June 2021) - Franchi, Francesco; Rollini, Fabiana; Been, Latonya; Maaliki, Naji; Abou Jaoude, Patrick; Rivas, Andrea; Zhou, Xuan; Jia, Sida; Briceno, Maryuri; Lee, Chang Hoon; Pineda, Andres M; Suryadevara, Siva; et al.
Abstract: Aims: Patients with diabetes mellitus (DM) and chronic kidney disease (CKD) are at increased risk of atherothrombotic events. Ticagrelor reduces ischaemic events compared to clopidogrel, with the greatest risk reduction in patients with both DM and CKD. How CKD status affects the pharmacodynamic (PD) and pharmacokinetic (PK) profiles of different ticagrelor maintenance dose regimens in patients with DM is unknown. Methods and results: In this randomized, crossover study, patients with DM on treatment with dual antiplatelet therapy (aspirin and clopidogrel) were stratified according to CKD status and randomized to ticagrelor 90 or 60 mg bid. PK/PD assessments were performed at baseline, after 7–10 days of ticagrelor (peak and trough), and after 7–10 days of alternative ticagrelor regimen (peak and trough). PK assessments included plasma concentrations of ticagrelor and its major metabolite. PD assessments included vasodilator-stimulated phosphoprotein (VASP)–platelet reactivity index (PRI), VerifyNow P2Y12, and light transmittance aggregometry (LTA). A total of 92 patients with DM (CKD, n  = 44; non-CKD, n  = 48) were randomized. Levels of platelet reactivity were lower with the 90 mg compared with the 60 mg ticagrelor dose, which was statistically significant in non-CKD but not in CKD patients for most PD measures. There were no significant differences in the primary endpoint (trough levels of VASP–PRI following ticagrelor 90 mg dosing) between cohorts (31 ± 20 vs. 25 ± 14; P  = 0.105). VerifyNow and LTA provided similar findings. PK assessments tracked PD profiles showing increased plasma concentrations of ticagrelor and its major metabolite in CKD compared to non-CKD patients. Conclusion: In patients with DM, although ticagrelor maintenance dose regimens (60 and 90 mg) yield potent P2Y12 inhibition, levels of platelet reactivity tended to be higher and subject to broader variability in non-CKD compared with CKD patients. Clinical trial registration: http://www.clinicaltrials.gov Unique Identifier: NCT02539160.